Analytical Chemistry (IntechOpen, 2023)
Analytical insight of materials provides a lucid pathway for further opportunities in the development of high-potential modified materials. The analytical assessment also enhances the probability of finding suitable materials for various applications. This book presents the latest advancements and applications of analytical chemistry in a systematic manner. It is an anthology of scientific findings and views of researchers from various research centers across the globe on emerging topics of instrumentation, energy, environment, biotechnology, and synthetic enhancement analysis techniques related to analytical chemistry. The volume contains twelve chapters containing discussion, analogies, and graphics for a better understanding of the presented concepts.